ARE NEUROLOGISTS MISSING THE POINT?. Issue 12 (15th November 2016) - Hurford, Robert; Bhuller, Cara; Bright, Liz; Crawley, Francesca
Abstract : Introduction: Using atraumatic needles for diagnostic lumbar puncture (LP) reduces the incidence of post-LP headache, but they are not commonly used in UK practice (Davis, 2014). We aimed to identify the reasons for this in our Trust and develop an appropriate teaching programme. Methods: We identified 28 trainees in one DGH for whom LP is an essential procedure (CMTs and medical SpRs). They completed a structured questionnaire between November and January 2015. Results: there were 17 (60.7%) completed questionnaires. The concept of a pre-prepared LP kit was rated 9.6 on a 10-point desirability scale. 14 (64.7%) respondents had never used the existing pack, and it was rated 2.7 on a 10-point usability scale. 14 (82.4%) respondents took more than 16 minutes to locate additional equipment. 3 (17.6%) respondents were aware of the benefits of atraumatic needles. Conclusion: we subsequently secured funding from the Deanery for an appropriate teaching package. This included lecture slides and practice with mannequins and has been delivered three times. We re-designed LP packs to include all necessary equipment, making pencil-point needles and protocols accessible. Cutting needles have been removed from the Trust. The success of these interventions are being assessed with a repeat questionnaire.